TINJAUAN HUKUM ISLAM TERHADAP PRAKTIK INVESTASI BERBENTUK ARISAN (Studi Kasus pada Komunitas Yud’s Money Machine di Surabaya) - saiful sulum (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2019)
AbstrakField research was conducted at the Yud’s Money Machine community in Surabaya with the aim at answering how investment practices based on arisan systems are owned by the community of Yud’s Money Machine in Surabaya, as well as Islamic perspective regarding such investment practices.The method used in this study is a qualitative method, i.e. a research paradigm to describe events, phenomena, behavior of people or situations in a particular place in detail and in-depth in the form of narration. This type of research is field research. As for the approach used there, it is is a case study namely a qualitative approach that examines certain "cases" in the context or arrangement of contemporary real life. Case studies are a type of in-depth research about individuals, one group, one organization, one activity program, and so on for a certain period of time. Data is collected by observation, interview and documentation techniques.The results of this study found that investment practices based on arisan systems in the community of Yud's Money Machine in Surabaya showed that the investment proceeds were very large, namely seventy-five percent of the capital paid in accordance with the contract set at the beginning of the contract regardless of the risk that would occur in the future. Because the most important thing in the investment transaction based on the arisan system is that it is only a very large profit, the element of seeking profit as much as possible and the determination of profit at the beginning of the contract is contrary to the investment system in Islam. It is because basically investment profits may not be set at the beginning of the contract because humans cannot know exactly what will happen in the future and this violates the nature that Allah has established, because only Allah Allah SWT will know what will happen in the future. Therefore, in the practice of investment transactions which is based on the arisan system in the community of Yud’s Money Machine in Surabaya, there are elements of usury fadl although the purpose is for the common good and providing help for members. It is not justified to take advantage in a way that is prohibited and contrary to Islamic law.Keywords: Islamic Law, Investment, Arisan.